Foregut ossicles morphology and feeding of the freshwater anomuran crab Aegla uruguayana (Decapoda, Aeglidae). - Williner, Verónica (2010)
The acquisition and processing of food is critical to animal survival and reproductive success. This work describes the foregut ossicles of Aegla uruguayana, which have been proposed to impart trophic characteristics. In addition, stomach contents were analyzed using IRI and RW indexes to characterize the diet. The Pearre index was applied to analyze trophic selectivity. We found A. uruguayana has a morphological foregut typical of macrophage organisms. Stomach contents included items typical of omnivorous, generalist, and opportunistic feeding modes. Vegetal remains included algae (filamentous, unicellular and colonial morphotypes), insect larvae, oligochaetes, microcrustaceans (copepods and cladocerans), mites, tardigrades, juveniles of A. uruguayana, and rotifers. Morphological descriptions of the foregut can reveal feeding habits and provide data on the possible trophic profile of a species, while guiding the selection of appropriate methodology for subsequent analysis. Our stomach content data corroborated the foregut description, but the presence of small prey suggested A. uruguayana utilizes both predation and detritivory trophic strategies.